Tell-tale signals: faces reveal playful and aggressive mood in wolves - Maglieri V.; Mastrandrea F.; Galotti A.; Boye M.; Laurent S.; Marcolla A.; Palagi E. (Animal Behaviour, 2024)
Animals have evolved a wide variety of signals that punctuate social interactions, thus optimizing communication systems. In the study of communicative strategies, real and play fighting are good models, as they are associated with risks and injuries. Therefore, within these two domains, clear ‘statement’ signals should be recruited to disambiguate messages. We gathered video data (135 h) from 38 wolves from three mixed-age captive groups (Canis lupus arctos, C. l. lupus, C. l. occidentalis) and analysed all the facial expressions in aggressive and playful domains. The analyses revealed the presence of three different threatening faces (Light-, Medium- and High-TF), mainly performed during aggressive encounters, which differed in the degree of mouth opening and lip stretching. We also identified two different relaxed open mouth facial expressions (Full- and Half-ROM) exclusively performed during play and possibly signalling different levels of playful arousal. Interestingly, facial expressions did not differ between groups thus suggesting a hard-wired facial communication system at least in these two domains. The next step will be to test hypotheses on the efficacy of such facial displays in eliciting an appropriate response in the receivers, potentially translating into a fine modulation of behavioural patterns in both play and real fighting.